Adecuación de un equipo de transmisión y recepción de FM, para fines didácticos y elaboración de su documentación técnica. - Flores Gaona, Carlos Eduardo (2005)
The present project is based on the study of a transmission-reception team, preparation of its technical documentation and implementation in the laboratory for didactic purposes, which will undoubtedly become an important study support for professionals in training. Communications have been developing at giant steps in such a way that it is very difficult to understand the means and technologies used to achieve them. That is why we present this project to study each of the parts that make up a transmission-reception in which we explain how they work and the relationship that exists between one and the other to produce the communication of audio and data contained in modules In each of the blocks. In chapter I we will discuss the power supplies used for each of the modules, the circuit diagrams and a brief explanation about the voltage sources. Chapter II deals with frequency modulation, all that influences the occurrence of this phenomenon. This chapter has been divided into eight important topics such as: • Attenuation • AF-RF amplifier • The modulator • The RF oscillator • Frequency Amplifier • Filters • Automatic Frequency Control Chapter III deals with what is Demodulation, all the steps that the reception function from the detection of signal that carries through a series of stages like amplifiers, mixers, etc .; The demodulation performs a function contrary to the modulation step. The signal detected by the equipment is translated at audible and understandable frequencies for the human being. As well as the modules presented in this part of the team. The annexes contain all the plans, the translation and prescription of the Tx-Rx operating manual of each of the blocks that will facilitate the use of it and photos of the equipment. Finally, it is noted the part of conclusions and recommendations that have been presented in the development of this project.